Reforming the Corporate Governance of Italian Banks - Jassaud, Nadege (IMF Working Papers; Working Paper ;, 2014)
Sound corporate governance is essential for a well-functioning banking system and the integrity of financial markets. The paper discusses the corporate governance of Italian banks, its regulatory framework, and the specific challenges arising from the role played by foundations and large cooperatives. Although Italian banks have recently made progress in improving their corporate governance, more needs to be done. In this regard, further improvements should include: (i) strengthening further the existing banking regulations through stricter fit-and-proper rules for directors and controlling shareholders; (ii) implementing the new related party lending regulation with tightened definitions; (iii) strengthening oversight of foundations when they are the controlling shareholders in banks; and (iv) facilitating the transformation of large cooperatives into joint stock companies.